Impact of Corporate Governance and Timeliness of Financial Reporting on the Performance of Nepalese Commercial Banks - Pradhan, Priya; Jha, Puja; Sah, Puja; Magar, Ram Bahadur (Nepalese Journal of Business, 2024)
This study examines the impact of corporate governance and timeliness of financial reporting on the performance of Nepalese commercial banks. Return on assets and return on equity are selected as the dependent variables. Similarly, board size, leverage, audit committee size, annual general meeting delay, board meeting and independent directors are selected as the independent variables. This study is based on secondary data of 17 commercial banks with 119 observations for the study period from 2015/16 to 2021/22. The data were collected from Banking and Financial statistics published by Nepal Rastra bank and the annual reports of respective banks. The correlation coefficients and regression models are estimated to test the significance and importance of corporate governance on the timeliness of financial reporting in Nepalese commercial banks. The study revealed that board size has a negative impact on return on assets and return on equity. It means that increase in board size leads to decrease in return on assets and return on equity. Likewise, leverage ratio has a positive impact on return on equity. It shows that higher the leverage ratio, higher would be the return on equity. Similarly, leverage ratio has a negative impact on return on assets. It shows that higher the leverage ratio, lower would be the return on assets. Moreover, this study showed that audit committee has a positive impact on return on assets and return on equity. It means that increase in audit committee leads to increase in return on assets and return on equity. Further, annual general meeting has a negative impact on return on equity. It shows that higher the annual general meeting, lower would be the return on equity. In addition, annual general meeting has a positive impact on return on assets. It shows that higher the annual general meeting, higher would be the return on assets. Likewise, board meetings have a positive impact on return on assets and return on equity. It shows that higher the board meetings, higher would be the return on assets and return on equity. Likewise, independent director has a negative impact on return on equity. It indicates that increase in independent director leads to decrease in return on equity. Similarly, independent director has a positive impact on return on assets. It indicates that increase in independent director leads to increase in return on assets.